Strategic Trade Policy and the Home Bias in Firm Ownership Structure - Steffen Huck; Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this note we consider the preferences of a profit maximizing firm for international ownership in a world in which firms compete in an international Cournot oligopoly, and in which countries use strategic trade policy. We find that firms prefer national ownership and show that full indigenisation occurs in the equilibrium.
Keywords: 330; strategic trade; international ownership; Cournot oligopoly; home bias